Perdagangan Internasional sebagai Pendorong Pertumbuhan Ekonomi Negara Berkembang: A Systematic Literature Review - Bunga Aprilia; Rizi Fitri Yani; Vera Afriani Saputri; Nurwahidah Sartika (CV. ITTC INDONESIA, 2026)
Global trade is a crucial element contributing to the economic advancement of developing nations through export and import activities. This study aims to explore the role of global trade in enhancing the economic growth of developing countries while identifying the various factors influencing its effectiveness. A Systematic Literature Review (SLR) methodology was employed, examining five scholarly works published between 2016 and 2026 that address the relationship between global trade and economic growth. Data were gathered from diverse academic journals and analyzed using a thematic analysis method. The findings indicate that global trade has a positive impact on economic growth, evidenced by increases in Gross Domestic Product (GDP), foreign exchange earnings, investment, productivity, and economic sector competitiveness. Exports emerge as a primary driver of economic growth, whereas imports can yield positive outcomes when utilized to support domestic production processes. Furthermore, the effectiveness of global trade is influenced by government policies, human resource quality, economic stability, and the industrial sector's ability to withstand global competition. Consequently, international trade can serve as a vital strategy for fostering sustainable economic growth in developing nations, provided it is supported by appropriate policies and the strengthening of local economic capacity.